At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
The base of the tent measures 96 inches wide, and the length from the top point of the tent to the corners of the base is 102 inches.
What is the length of the pole that Daniel needs to support the middle of the tent?
Use pythagoras' theorem :)
how do u suppose i do dat?
imagine a line from the top point to the middle of the base. You now have two right angled triangles. Use pythagoras' theorem on one to find the height (the line you've drawn in) a^2+b^2=c^2 a=96/2=48 b=the height c=102 48^2+b^2=102^2 2304+b^2=10404 b^2=10404-2304=8100 b=sqrt(8100) b=90
A. 72 inches B. 180 inches C. 96 inches D. 90 inches
b=90, so b is answer D! Do you understand it?
use pythagoras' theorem again. in this case: a=sqrt(40) b=3 c=z on the diagram so: sqrt(40)^2+3^2=c^2 40+9=c^2 49=c^2 c=sqrt(49) c=7 :)
are you actually understanding this or just taking the answers? if you're learning you should be able to work this out now. remember, for right angled triangles, just use pythagoras' theorem!
im having trouble with the squareroot part
what exactly do you mean? :)
are you doing the question you attached? how does the sqrt(15) come into it?
im doing em i just dont understand em
so you are doing the attached one? do you know pythagoras' theorem?
yes and yes a^2+b^2=c^2
correct :) in this case you need to find a, so rearrange the equation so that a is by itself
but the square root how do i figure that
when you rearrange, the equation is: a^2=c^2-b^2 i think you mean sqrt(53)=z? In pythagoras' theorem, the z is the equivalent of c because it is the hypotenuse, so you subsitute this into the equation: a^2=sqrt(53)^2-b^2 when you square a square root, you're basically just getting rid of the square root, so sqrt(53)^2=53 does that help?
good, so you can answer the question now? :)